2020
DOI: 10.1016/j.chaos.2020.110212
|View full text |Cite
|
Sign up to set email alerts
|

Predictions for COVID-19 with deep learning models of LSTM, GRU and Bi-LSTM

Abstract: COVID-19, responsible of infecting billions of people and economy across the globe, requires detailed study of the trend it follows to develop adequate short-term prediction models for forecasting the number of future cases. In this perspective, it is possible to develop strategic planning in the public health system to avoid deaths as well as managing patients. In this paper, proposed forecast models comprising autoregressive integrated moving average (ARIMA), support vector regression (SVR), long shot term m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
352
1
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 587 publications
(366 citation statements)
references
References 25 publications
6
352
1
7
Order By: Relevance
“…The best model occurs in S6, which means that the bi-directional architecture performs better than the single directional architecture for two-day-ahead forecasting after hyperparameter optimisation. The outperformance of the bi-directional architecture has been claimed by many studies [52,53,60,66] in other domains and is still supported by this research when applying to runoff forecasting.…”
Section: Overall Evaluationsupporting
confidence: 72%
See 1 more Smart Citation
“…The best model occurs in S6, which means that the bi-directional architecture performs better than the single directional architecture for two-day-ahead forecasting after hyperparameter optimisation. The outperformance of the bi-directional architecture has been claimed by many studies [52,53,60,66] in other domains and is still supported by this research when applying to runoff forecasting.…”
Section: Overall Evaluationsupporting
confidence: 72%
“…Another study [51] shows that a better prediction result (the test NSE of 0.942 compared with 0.666) has been obtained when using a selected subset of all rain gauges as the input. Furthermore, the LSTM or GRU networks' architectures can also influence the forecasting results [52,53].…”
Section: Introductionmentioning
confidence: 99%
“…Also, in [9] , a new ensemble approach based on ANNs and fuzzy aggregation was proposed and its performance was evaluated on COVID-19 time series of Mexico and its 12 states which showed significant improvement than single ANN. In recent studies [ 2 , [10] , [11] , [12] ], deep learning methods such as LSTM and bidirectional LSTM (BiLSTM) have been utilized for COVID-19 time series forecasting . The results indicated that LSTM and its variants have good performance in predicting the COVID-19 time series.…”
Section: Introductionmentioning
confidence: 99%
“… Zeroual et al, 2020 , Tomar and Gupta, 2020 , Czarnowski et al, 2008 , El Zowalaty and JĂ€rhult, 2020 , Shahid et al, 2020 , Hewamalage et al, 2021 , JimĂ©nez et al, 2020 , Kaushik et al, 2020 , BhedadJamshidi et al, 2020 , Ribeiro et al, 2020 , NaudĂ©, 2020 , Arora et al, 2020 , Ribeiro et al, 2020 , Ogundokun et al, 2020 , Alzahrani et al, 2020 , Shastri et al, 2020 , Alakus and Turkoglu, 2020 , Papastefanopoulos et al, 2020 , Chimmula and Zhang, 2020 , Wang et al, 2020 , Wang et al, 2020 , DataGov , Car et al, 2020 .…”
Section: Uncited Referencesmentioning
confidence: 99%